A Systematic Review and Meta-Analysis of Studies Comparing Concurrent Chemoradiotherapy With Radiotherapy Alone in the Treatment of Stage II Nasopharyngeal Carcinoma - Xu, Yao-Can; Chen, Kai-Hua; Liang, Zhong-Guo; Zhu, Xiao-Dong (Frontiers in Oncology, 2022)
Purpose: The role of Concurrent Chemoradiotherapy (CCRT) in stage II nasopharyngeal carcinoma (NPC) is still controversial. Our objective is to evaluate the value of concurrent chemotherapy in stage II NPC receiving radiotherapy (RT). Methods: We searched the PubMed, Embase, and Scopus databases for studies comparing CCRT versus RT alone in stage II NPC with survival outcomes and toxicities, including locoregional recurrence-free survival (LRFS), metastasis-free survival (DMFS), progression-free survival (PFS), overall survival (OS), and grade 3-4 acute toxicities. The hazard ratios (HRs) of survival outcomes and risk ratios (RRs) of toxicities were extracted for meta-analysis. Subgroup analysis for stage N1 patients was performed to further explore whether these populations can earn benefits from concurrent chemotherapy. Results: Nine eligible studies with a total of 4092 patients were included. CCRT was associated with a better OS (HR=0.61, 95% CI 0.44–0.82), LRFS (HR=0.62, 95% CI 0.50–0.78), and PFS (HR=0.65, 95% CI 0.54–0.79), but with similar DMFS (HR = 0.81, 95% CI = 0.46-1.45) compared with two-dimensional RT (2DRT) alone. However, CCRT showed no survival benefit in terms of OS (HR=0.84, 95% CI 0.62–1.15), LRFS (HR=0.85, 95% CI 0.54–1.34), DMFS (HR=0.96, 95% CI 0.60–1.54) and PFS (HR=0.96, 95% CI 0.66–1.37) compared with intensity modulated RT (IMRT) alone. Subgroup analyses indicated that CCRT had similar OS (HR=1.04, 95% CI 0.37–2.96), LRFS (HR=0.70, 95% CI 0.34–1.45), DMFS (HR=1.03, 95% CI 0.53–2.00) and PFS (HR=1.04, 95% CI 0.58–1.88) in the stage N1 populations. Meanwhile, compared to RT alone, CCRT significantly increased the incidence of grade 3-4 leukopenia (RR = 4.00, 95% CI 2.29–6.97), mucositis (RR = 1.43, 95% CI 1.16–1.77), gastrointestinal reactions (RR = 8.76, 95% CI 2.63–29.12). No significant differences of grade 3–4 toxicity in thrombocytopenia (RR = 3.45, 95% CI 0.85–13.94) was found between the two groups. Conclusion: For unselected patients with stage II NPC, CCRT was superior to 2DRT alone with better LRFS, PFS and OS, while adding concurrent chemotherapy to IMRT did not significantly improve survival but exacerbated acute toxicities.